Estudio de prefactibilidad para la instalación de una planta productora de mantequilla a base de cashew (Anacardium occidentale) - Plasencia Caipo, Sebastian Cesar (2022)
The present investigation raises the economic, financial, technical, market, technological and social viability of the installation of a production plant of a butter based on cashew nut. Cashew butter is an energetic product that contains nutritional benefits such as zero cholesterol, unsaturated fats, protein, high levels of magnesium, iron, zinc, phosphorus. The target market will be sectors A, B and C of Metropolitan Lima of all ages and of both genders. Through the surveys, a purchase intention of 69.80% was identified with an estimated demand for the first year of 46,497.4 kg of finished product that is equivalent to 185,989 jars in 250-gram presentation, reaching a demand of 256,633 jars after five years of useful life of the project. Based on the study of micro and macro location, it was identified that the best option for the location of the plant will be in Lurín in the department of Metropolitan Lima. In addition, the necessary and required technologies were found to carry out the butter production process and using the dimensions and the Guerchet method, a plant area of 330 m2 and a plant capacity of 977,433 jars per year were determined. On the economic side, performing the necessary calculations, an economic NPV of S /. 130,452.23, an IRR of 22.13%, which is higher than the opportunity cost of 15.53%. On the financial side, performing the necessary calculations, a financial NPV of S /. 173,107.15, an IRR of 30.52%, in the same way higher than the opportunity cost which is 15.53%. Finally, according to the market, technological, economic, financial and social evaluation, it can be concluded that the installation of a cashew butter production plant is viable